The Effect of Modified Lunch Animal Side Dishes on Leftovers in Patients On A Regular Rice Diet - Rismawati Rismawati; Rusmini Yanti; Rijanti Abdurrachim; Niken Widyastuti Hariati (Indonesian Journal of Global Health Research, 2026)
Food waste is an important indicator of the quality of hospital nutrition services and influences the adequacy of patient intake. Data from Dr. H. Andi Abdurrahman Noor Regional General Hospital (RSUD) in 2025 showed that animal side dishes at lunch had the highest waste, particularly omelettes and fried catfish. This study aimed to assess the effect of modified animal side dishes on animal side dish waste in hospitalized patients on a regular rice diet. The study used a quasi-experimental design with a control and intervention group. A total of 72 patients were selected purposively, consisting of 36 patients who received standard side dishes and 36 patients who received modified side dishes (fried egg balado, sweet and sour catfish, and crispy catfish). Food waste was measured using the Comstock method, while sensory assessments were obtained through a questionnaire with validity test results showed that all sensory assessment questionnaire items had a calculated r value > r table (0.30), thus being declared valid. The reliability test results for the sensory assessment questionnaire showed a Cronbach's Alpha value of 0.82, indicating a reliable instrument. The statistical test used was the independent mean difference test (T-independent test).  The results showed that standard side dishes had a very high percentage of food waste. After modification, the average food waste decreased significantly (p = 0.001). Consumption of modified side dishes increased, with the "good" category reaching 63.9% for fried egg balado, 69.44% for sweet and sour patin, and 59.4% for crispy patin. This study concluded that modifying animal side dishes effectively reduced food waste and increased patient sensory acceptance.